Characterizing the Chemical Contaminants Diversity and Toxic Potential of Untreated Wastewater From a Drug Rehabilitation Hospital: Understanding Impact on Downstream Environment - Baasher, Fras; Wang, Tian-Nyu; Zulhelmi Bin Yusnan, Muhammad; Alkahtani, Mohsen; Bashawri, Yasir M.; Al Qarni, Hamed; Hong, Pei-Ying (Frontiers in Environmental Science, 2022)
This study characterizes a total of 21 wastewater samples collected from Al Amal hospital, and aims to determine if untreated hospital wastewater may impose a potentially detrimental impact on the downstream municipal biological wastewater treatment process. By means of solid phase extraction and liquid chromatography with tandem mass spectrometry (LC-MS/MS), chemical contaminants in these wastewater samples were determined in a non-targeted manner. In-silico characterization for the mutagenicity and reactive oxygen species (ROS) producing capabilities was performed by checking against database and literature. However, majority of the chemical contaminants have no prior information available and remain uncharacterized for both traits. Instead, in-vitro mutagenicity tests by means of Ames test showed that majority of the samples were non-mutagenic except for 5 samples that imposed mutagenic effect at high concentrations of >10x. In-vitro tests to determine for intracellular ROS production further showed that one of the mutagenic samples collected on Jun-22 positively induce ROS production and subsequently increased horizontal gene transfer via natural transformation. The findings in this study suggest that a specialty hospital like Al Amal does not frequently contribute mutagenic compounds and ROS to the wastewater streams, and hence unlikely to significantly perturb the downstream environment. However, there may still be a need to consider potential accumulation of these chemical compounds, as well as ad-hoc contributions of mutagenic and/or toxic wastewater streams from the hospitals towards horizontal gene transfer.